Environmental Sustainability: Key to Achieving Other Millennium Development Goals (MDGs). - Yusuf, Babatunde Rahman; Idowu, Khadijah A.; Adebayo, Mudashiru A.; Yaqub, Jemilah (IJRDO - Journal of Business Management, 2015)
Millennium Development Goals are grounded in the recognition of the role played by theenvironment and natural resources in providing the material and environmental basis, theecosystems, and the energy on which economic processes depend. This study sets out to establishan association model between environmental sustainability (MDG 7) and the achievement of theMillennium Development Goals. This study stems from the fact that environmental sustainabilityis the key to the achievement of all the MDGs which focuses on the environmental impacts ofurban agglomerations, as it aims to improve the lives of 100 million urban slum dwellersby2015. The study adopted a descriptive research design and was guided by seven researchquestions. 637 respondents were randomly sampled and analyzed using regression. The resultsshow that there is a relationship between Environmental Sustainability (ES) and the achievementof the Millennium Development Goals. The study recommends that population growth should belinked to environmental sustainability for the achievement of Millennium Development Goals(MDGs).